Next Generation Hairpin Polyamides with (R)-3,4-Diaminobutyric Acid Turn Unit - Dose, Christian (2008)
The characterization of a new class of pyrrole–imidazole hairpin polyamides with β-amino-γ-turn units for recognition of the DNA minor groove is reported. A library of eight hairpins containing (R)-and (S)-3,4-diaminobutyric acid (β-amino-γ-turn) has been synthesized, and the impact of the molecules on DNA-duplex stabilization was studied for comparison with the parent γ-aminobutyric acid (γ-turn) and standard (R)-2,4-diaminobutyric acid (α-amino-γ-turn)-linked eight-ring polyamides. For some, but not all, sequence compositions, melting temperature analyses have revealed that both enantiomeric forms of the β-amino-γ-turn increase the DNA-binding affinity of polyamides relative to the (R)-α-amino-γ-turn. The (R)- β-amine residue may be an attractive alternative for constructing hairpin polyamide conjugates. Biological assays have shown that (R)- β-amino-γ-turn hairpins are able to inhibit androgen receptor-mediated gene expression in cell culture similar to hairpins bearing the standard (R)-α-amino-γ-turn, from which we infer they are cell-permeable.